A dimensão política da educação ambiental em investigações de revistas brasileiras de ensino de ciências - Santos, Wildson Luiz Pereira dos; Carvalho, Luiz Marcelo de [UNESP]; Levinson, Ralph (My University, 2014)
Through an analysis of texts linking environmental education to science education, this article aims to highlight the political dimensions of democracy, citizenship and social justice. It seeks to emphasize the context of compulsory education that has privileged research on certain curriculum areas, environmental issues and topics that have been selected by the researchers. The analyses indicated a slight predominance of critical perspectives on environmental education as a preferred theoretical framework. Taking into consideration that there are societal models underlying the consensus on this dimension that remain hidden and need to be brought out into the open to be critically discussed, we propose more clarification in this point. Likewise, we conclude that there is a need for greater clarification of the meaning of the political dimension of environmental education.

O presente texto tem como objetivo sistematizar resultados relacionados com a dimensão política da educação ambiental apresentada em artigos que estabelecem relações entre educação ambiental e o ensino das Ciências da Natureza, destacando aspectos em termos de democracia, cidadania e justiça social. Busca-se evidenciar o contexto da educação básica que tem sido privilegiado nessas pesquisas, tais como, áreas curriculares, temas ambientais, temas de estudo que têm sido selecionados pelos investigadores que se voltam para essa temática. As análises apontam certa predominância das perspectivas críticas em educação ambiental como referencial teórico. Por outro lado, constata-se que a dimensão política tem sido pouco considerada como foco de investigação e nas conclusões dos artigos analisados. Conclui-se, pela necessidade de maior explicitação sobre sentidos do que vem a ser a dimensão política da educação ambiental, pois por de trás dos consensos em torno dessa dimensão se escondem modelos de sociedade e de democracia que precisam ser discutidos.
The political dimension of environmental education into research of brazilian journals of science education
Keywords: Environmental education; Political dimension of environmental education; Science education; Research in science education; Research in environmental education; Educação ambiental; Dimensão política da educação ambiental; Ensino de Ciências da Natureza; Pesquisa em ensino de Ciências da Natureza; Pesquisa em educação ambiental